Chloride Induced Stress Corrosion Cracking For Thermally Insulated Austenitic Stainless Steel Type 304 Using Wick Test - RAVI, RUBEN (IRC, 2021)
Stress corrosion cracking (SCC) is a failure mechanism that takes place under residual stress conditions for various alloy/material and environmental combinations.